AN ANALYSIS OF VERBAL AND NONVERBAL SIGNS FOUND IN BMW CAR ADVERTISEMENTS - Ni Putu Dian Ratna Sari (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
This study is concerned about analyzing verbal and non-verbal signs in the BMW car series and the meaning of verbal and non-verbal signs in the BMW car series. This study used a qualitative method to collect data and data obtained from print advertisements for BMW series 1 and BMW 3 series. The theory used in this research is semiotic theory of Saussure cites Chandler (2006)'s analysis of the meaning of verbal and non-verbal signs in the BMW car series based on Barthes' (1967) theory of meaning. This study found 6 verbal signs and 7 non-verbal signs, 12 connotative and 3 denotative meanings. The dominant data contains connotative meanings in advertisements because advertisements have hidden meanings that the company wants to convey it can see from the non-verbal signs in advertisements such as color, picture and symbol. It also to attract readers attention and provide information about the advantages and also the features of BMW Car Series products.